The effect of realistic mathematical approaches towards the students' math learning outcomes - Qomario, Qomario; Tohir, Ahmad; Mashari, Ali (Jurnal Prima Edukasia, 2020)
This research aimed to describe the effect of realistic mathematical approaches on mathematics learning outcomes of fourth grade students at SDN 4 JatiMulyo. Type of this research is quantitative research using quasi-experimental methods and using one-group pre-test and post-test design. This research is conducted for grade IV odd semester 2019/2020 at SDN 4 JatiMulyo. The population in this research are all fourth grade students of SDN 4 Jati Mulyo with a total of 31 students. The sampling using saturated sampling technique (total sampling), thus the sample in this research amounted to 31 students. The data collection is done through tests, namely pre-test and post-test. The data analysis technique used in this study is descriptive analysis. Based on the result and discussion in this research, it can be concluded that there is an effect of a realistic mathematical approach to the mathematics learning outcomes of fourth grade students at SD N 4 JatiMulyo. This is evidenced by the mean value of mathematics learning outcomes is 83.84 (very good category). From these results it can be concluded that there was an effect of a realistic mathematical approach to student mathematics learning outcomes.